Adhesive sheet

The pressure-sensitive adhesive sheet with a composite adhesive layer addresses the issues of moire interference and uneven image display in liquid crystal display devices by reducing moire and enhancing durability, making it suitable for high temperature and high humidity environments.

JP7656446B2Active Publication Date: 2025-04-03LINTEC CORP
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2021033611
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-03
Publication Date
2025-04-03
Estimated Expiration
2041-03-03

AI Technical Summary

Technical Problem

Liquid crystal display devices experience moire interference and uneven image display due to interference between liquid crystal cells, and require high durability in high temperature and high humidity environments.

Method used

A pressure-sensitive adhesive sheet with a composite adhesive layer containing a light diffusing adhesive layer and a transparent adhesive layer, characterized by a dynamic hardness of 0.007 or more on the transparent adhesive layer side and a haze value of 70% or more to 99% or less, which reduces moire interference and enhances durability.

Benefits of technology

The adhesive sheet effectively prevents uneven display of moire and images when two liquid crystal cells are laminated, while maintaining excellent durability under high temperature and high humidity conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007656446000003
    Figure 0007656446000003
  • Figure 0007656446000004
    Figure 0007656446000004
  • Figure 0007656446000001
    Figure 0007656446000001
Patent Text Reader

Abstract

To provide an adhesive sheet that is less likely to cause moire patterns and unevenness in displayed images when, for example, two liquid crystal cells are bonded together.SOLUTION: An adhesive sheet 1 has a composite adhesive layer 2 that contains a light-diffusion adhesive layer 21 containing light-diffusion fine particles and a transparent adhesive layer 22 not containing light-diffusion fine particles. The transparent adhesive layer 22 side-surface is measured in its dynamic hardness (DHT115-1), which is 0.007 or more. The composite adhesive layer 2 has a haze value of 70% or more and 99% or less.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a pressure-sensitive adhesive sheet having light diffusing properties. [Background technology]

[0002] In recent years, stereoscopic image display devices that display images stereoscopically have been proposed as a type of display, and among them, liquid crystal display devices with a structure in which two liquid crystal cells are stacked are known (Patent Document 1, etc.). In such liquid crystal display devices, images are displayed stereoscopically by manipulating the brightness of the image in each liquid crystal cell and sending different light information to each eye. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2015-114371 A Summary of the Invention [Problem to be solved by the invention]

[0004] However, in such liquid crystal display devices, as the resolution of the displayed image increases, moire is likely to occur due to interference between liquid crystal cells, making the displayed image difficult to see. In addition, display devices such as liquid crystal display devices are required to display images without unevenness, and are required to have high durability in high-temperature and high-humidity environments, particularly when used for in-vehicle applications.

[0005] The present invention has been made in consideration of the above-mentioned circumstances, and aims to provide an adhesive sheet that is less likely to cause moire and uneven image display when, for example, two liquid crystal cells are bonded together, and that also has excellent durability. [Means for solving the problem]

[0006] In order to achieve the above-mentioned object, firstly, the present invention provides an adhesive sheet having a composite adhesive layer comprising a light diffusing adhesive layer containing light diffusing microparticles and a transparent adhesive layer not containing light diffusing microparticles, characterized in that the dynamic hardness (DHT115-1) measured on the surface on the transparent adhesive layer side is 0.007 or more, and the haze value of the composite adhesive layer is 70% or more and 99% or less (Invention 1).

[0007] According to the pressure-sensitive adhesive sheet of the above invention (Invention 1), due to the above-mentioned configuration and physical properties, when, for example, two liquid crystal cells are bonded together, moire and image display unevenness are unlikely to occur, and the sheet has excellent durability.

[0008] In the above invention (Invention 1), the dynamic hardness (DHT115-1) measured on the surface on the light diffusing pressure-sensitive adhesive layer side is preferably 0.007 or more (Invention 2).

[0009] In the above inventions (Inventions 1 and 2), the adhesive strength of the surface on the transparent adhesive layer side to soda lime glass is preferably 1 N / 25 mm or more and 80 N / 25 mm or less (Invention 3).

[0010] In the above inventions (Inventions 1 to 3), the adhesive strength of the surface on the light diffusing pressure-sensitive adhesive layer side to soda-lime glass is preferably 1 N / 25 mm or more and 80 N / 25 mm or less (Invention 4).

[0011] In the above inventions (Inventions 1 to 4), the thickness of the composite pressure-sensitive adhesive layer is preferably 70 μm or more and 3000 μm or less (Invention 5).

[0012] In the above inventions (Inventions 1 to 5), it is preferable that two release sheets are provided and the composite pressure-sensitive adhesive layer is sandwiched between the release sheets so as to be in contact with the release surfaces of the two release sheets (Invention 6).

[0013] In the above inventions (Inventions 1 to 6), it is preferable that the sheet is used to bond two hard plates together (Invention 7).

[0014] Secondly, the present invention provides an adhesive sheet having a composite adhesive layer comprising a light diffusing adhesive layer containing light diffusing microparticles and a transparent adhesive layer not containing light diffusing microparticles, wherein the transparent adhesive layer has a storage shear modulus G' of 0.07 MPa or more and 10 MPa or less, and the composite adhesive layer has a haze value of 70% or more and 99% or less (Invention 8).

[0015] In the above invention (Invention 8), the storage shear modulus G' of the light diffusing pressure-sensitive adhesive layer is preferably 0.07 MPa or more and 10 MPa or less (Invention 9). Effect of the Invention

[0016] According to the pressure-sensitive adhesive sheet of the present invention, when, for example, two liquid crystal cells are bonded together, moire and image display unevenness are unlikely to occur, and the sheet is also excellent in durability. [Brief description of the drawings]

[0017] [Figure 1] 1 is a cross-sectional view of a pressure-sensitive adhesive sheet according to one embodiment of the present invention. [Diagram 2] 1 is a cross-sectional view of a liquid crystal display member according to one embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0018] Hereinafter, an embodiment of the present invention will be described. [Adhesive sheet] The pressure-sensitive adhesive sheet according to one embodiment of the present invention has a composite pressure-sensitive adhesive layer including a light-diffusing pressure-sensitive adhesive layer containing light-diffusing microparticles and a transparent pressure-sensitive adhesive layer not containing light-diffusing microparticles. In this specification, "not containing light-diffusing microparticles" means "not substantially containing light-diffusing microparticles", and includes not only not containing any light-diffusing microparticles, but also containing light-diffusing microparticles in an amount that does not impair the effect of this embodiment. The amount is preferably 0.1% by mass or less, particularly preferably 0.01% by mass or less, more preferably 0.001% by mass or less, and most preferably 0% by mass.

[0019] In the pressure-sensitive adhesive sheet according to the present embodiment, the dynamic hardness (DHT115-1; hereinafter, sometimes omitted) measured on the surface on the transparent pressure-sensitive adhesive layer side is preferably 0.007 or more, and the haze value of the composite pressure-sensitive adhesive layer is preferably 70% or more and 99% or less. The method for measuring the dynamic hardness (DHT115-1) in this specification is as shown in the test examples described later. The haze value in this specification is a value measured in accordance with JIS K7136:2000.

[0020] In the pressure-sensitive adhesive sheet according to the present embodiment, the dynamic hardness is 0.007 or more, so that the sheet has excellent durability under high temperature and high humidity conditions. For example, in a laminate obtained by bonding two liquid crystal cells (glass plates in a test) via the composite pressure-sensitive adhesive layer of the pressure-sensitive adhesive sheet according to the present embodiment, even when the laminate is left under high temperature and high humidity conditions, for example, 60°C and 95% RH conditions, for 1000 hours, the occurrence of air bubbles and peeling is suppressed at the interface between the composite pressure-sensitive adhesive layer and the liquid crystal cell (glass plate).

[0021] Here, when liquid crystal cells, which are hard bodies, are bonded together by a pressure-sensitive adhesive layer, since neither of them has flexibility, the pressure-sensitive adhesive layer is compressed in the layer thickness direction, and the stress of the compression is stored in the pressure-sensitive adhesive layer. This residual stress acts as a repulsive force on the two liquid crystal cells. When the pressure-sensitive adhesive layer is a light-diffusing pressure-sensitive adhesive layer, it is presumed that the repulsive force is strong or weak (uneven) depending on the density (shade) of the light-diffusing fine particles per surface area in contact with the liquid crystal cell of the light-diffusing pressure-sensitive adhesive layer. It is presumed that the unevenness of the repulsive force of the pressure-sensitive adhesive layer against the liquid crystal cell caused in this way disturbs the orientation of the liquid crystal cell and causes unevenness in the displayed image. In the pressure-sensitive adhesive sheet according to this embodiment, the physical properties of the pressure-sensitive adhesive layer are defined by the dynamic hardness that represents the local elastic behavior from the surface of the pressure-sensitive adhesive layer to the thickness direction of the pressure-sensitive adhesive layer, thereby suppressing the unevenness of the displayed image.

[0022] In addition, as in the composite adhesive layer of the adhesive sheet according to the present embodiment, when a transparent adhesive layer that does not have light-diffusing microparticles is present in addition to the light-diffusing adhesive layer, it is presumed that the transparent adhesive layer can alleviate the stress unevenness caused by the density of the light-diffusing microparticles in the light-diffusing adhesive layer against the compression of the liquid crystal cells, which are two hard plates. This makes it possible to more effectively suppress the occurrence of unevenness in the displayed image. That is, by having the transparent adhesive layer as described above in addition to the light-diffusing adhesive layer, the prevention of image display unevenness caused by bonding liquid crystal cells together is improved.

[0023] In addition, in the pressure-sensitive adhesive sheet according to the present embodiment, the haze value of the composite pressure-sensitive adhesive layer is 70% or more, so that when two liquid crystal cells are bonded together using the composite pressure-sensitive adhesive layer, moire is unlikely to occur and image display unevenness is even less likely to occur. The haze value of the composite pressure-sensitive adhesive layer is 99% or less, so that visibility of the image displayed by the liquid crystal cell is ensured.

[0024] The dynamic hardness measured on the surface of the transparent adhesive layer is preferably 0.007 or more, more preferably 0.009 or more, particularly preferably 0.011 or more, and even more preferably 0.012 or more, from the viewpoint of the durability described above. Also, from the viewpoint of preventing display unevenness, the dynamic hardness is preferably 10 or less, more preferably 1 or less, particularly preferably 0.1 or less, and even more preferably 0.05 or less.

[0025] From the viewpoint of suppressing the occurrence of moire, the haze value of the composite pressure-sensitive adhesive layer is preferably 70% or more, more preferably 80% or more, particularly preferably 84% or more, further preferably 87% or more, and most preferably 90% or more. From the viewpoint of visibility of the displayed image, the haze value of the composite pressure-sensitive adhesive layer is preferably 99% or less, more preferably 98% or less, and particularly preferably 97% or less.

[0026] The dynamic hardness measured on the surface of the light-diffusing adhesive layer is preferably 0.007 or more, more preferably 0.009 or more, particularly preferably 0.010 or more, and even more preferably 0.011 or more. This makes the durability of the laminate more excellent. On the other hand, from the viewpoint of preventing display unevenness, the dynamic hardness is preferably 10 or less, more preferably 1 or less, particularly preferably 0.1 or less, and even more preferably 0.05 or less.

[0027] The storage shear modulus G' of the transparent pressure-sensitive adhesive layer and the storage shear modulus G' of the light-diffusing pressure-sensitive adhesive layer are preferably within the ranges specified in the embodiments described below. This makes it easier for the dynamic hardness to fall within the above-mentioned range. The method for measuring the storage shear modulus G' in this specification is as shown in the test examples described below.

[0028] The gel fraction of the adhesive constituting the transparent adhesive layer is preferably 30% or more, more preferably 40% or more, particularly preferably 50% or more, and even more preferably 55% or more. The gel fraction is preferably 90% or less, more preferably 80% or less, particularly preferably 70% or less, and even more preferably 60% or less. When the gel fraction is in the above range, the dynamic hardness and storage shear modulus G' of the transparent adhesive layer tend to be in a preferred range. The method for measuring the gel fraction of the adhesive in this specification is as shown in the test example described later.

[0029] The gel fraction of the adhesive constituting the light-diffusing adhesive layer is preferably 30% or more, more preferably 40% or more, particularly preferably 50% or more, and even more preferably 55% or more. The gel fraction is preferably 90% or less, more preferably 80% or less, particularly preferably 70% or less, and even more preferably 65% ​​or less. When the gel fraction is in the above range, the dynamic hardness and storage shear modulus G' of the light-diffusing adhesive layer tend to be in the preferred range.

[0030] In this embodiment, the composite pressure-sensitive adhesive layer may be composed of two layers, a light-diffusing pressure-sensitive adhesive layer and a transparent pressure-sensitive adhesive layer, or may be composed of three layers, a transparent pressure-sensitive adhesive layer, a light-diffusing pressure-sensitive adhesive layer and a transparent pressure-sensitive adhesive layer, laminated in that order. A preferred example of the composite pressure-sensitive adhesive layer in this embodiment is composed of two layers, a light-diffusing pressure-sensitive adhesive layer and a transparent pressure-sensitive adhesive layer, which will be described below with reference to the drawings.

[0031] As shown in Fig. 1, the adhesive sheet 1 according to this embodiment is composed of two release sheets 3a, 3b and a composite adhesive layer 2 sandwiched between the two release sheets 3a, 3b so as to be in contact with the release surfaces of the two release sheets 3a, 3b. However, the release sheets 3a, 3b are not essential components of the adhesive sheet 1, and are peeled off and removed when the adhesive sheet 1 is used. In this specification, the release surface of the release sheet refers to the surface of the release sheet that has releasability, and includes both a surface that has been subjected to a release treatment and a surface that exhibits releasability even without being subjected to a release treatment.

[0032] The composite pressure-sensitive adhesive layer 2 in this embodiment is composed of two layers: a light-diffusing pressure-sensitive adhesive layer 21 in contact with the release sheet 3a, and a transparent pressure-sensitive adhesive layer 22 in contact with the release sheet 3b.

[0033] 1. Each element 1-1. Composite adhesive layer The type of adhesive constituting the light diffusion adhesive layer 21 and the transparent adhesive layer 22 of the composite adhesive layer 2 in this embodiment is not particularly limited as long as the desired physical properties are obtained. For example, any of acrylic adhesives, polyester adhesives, polyurethane adhesives, rubber adhesives, silicone adhesives, etc. may be used. The adhesive may be any of emulsion type, solvent type, or solventless type, and may be any of crosslinked type or non-crosslinked type. Among them, acrylic adhesives that are excellent in adhesive properties, optical properties, etc. are preferred. As the acrylic adhesive, a crosslinked type is preferred, and a thermal crosslinked type is more preferred.

[0034] The adhesive constituting the light-diffusing adhesive layer 21 and the adhesive constituting the transparent adhesive layer 22 may be the same or different, but both are preferably acrylic adhesives, particularly non-active energy ray curable acrylic adhesives. This makes it easier to satisfy the above-mentioned physical properties (dynamic hardness and storage shear modulus G'). In this case, the compositions other than the light-diffusing fine particles may be the same or different. The monomer compositions of the main polymers may be the same or different.

[0035] Below, we will explain the case where the adhesive constituting the light-diffusing adhesive layer 21 and the adhesive constituting the transparent adhesive layer 22 are both acrylic adhesives that are not curable with active energy rays, but the present invention is not limited to this.

[0036] From the viewpoint of strengthening the cohesive force between the polymers, the adhesive constituting the light diffusing adhesive layer 21 and the adhesive constituting the transparent adhesive layer 22 are preferably formed by crosslinking an adhesive composition (hereinafter sometimes referred to as "adhesive composition P") containing a (meth)acrylic acid ester polymer (A) and a crosslinking agent (B). In the case of the light diffusing adhesive layer 21, the adhesive composition P further contains light diffusing fine particles (C).

[0037] The adhesive obtained from such adhesive composition P is likely to satisfy the above-mentioned physical properties (dynamic hardness, storage shear modulus G'), and can also exhibit desired optical properties, adhesive strength, etc. In this specification, (meth)acrylic acid means both acrylic acid and methacrylic acid. The same applies to other similar terms. In addition, the term "polymer" is also intended to include the concept of "copolymer."

[0038] (1) Components of the adhesive composition (1-1) (Meth)acrylic acid ester polymer (A) In the present embodiment, the (meth)acrylic acid ester polymer (A) preferably contains, as a monomer unit constituting the polymer, a reactive group-containing monomer having in the molecule a reactive group that reacts with the crosslinking agent (B). The reactive group derived from the reactive group-containing monomer reacts with the crosslinking agent (B) to form a crosslinked structure (three-dimensional network structure), thereby obtaining a pressure-sensitive adhesive having the desired cohesive strength.

[0039] Preferred examples of the reactive group-containing monomer include a monomer having a hydroxyl group in the molecule (hydroxyl group-containing monomer), a monomer having a carboxyl group in the molecule (carboxyl group-containing monomer), a monomer having an amino group in the molecule (amino group-containing monomer), etc. Among these, a hydroxyl group-containing monomer or a carboxyl group-containing monomer having excellent reactivity with the crosslinking agent (B) is preferred.

[0040] Examples of the hydroxyl group-containing monomer include (meth)acrylic acid hydroxyalkyl esters such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 3-hydroxybutyl (meth)acrylate, and 4-hydroxybutyl (meth)acrylate. Among them, from the viewpoint of the reactivity of the hydroxyl group in the obtained (meth)acrylic acid ester polymer (A) with the crosslinking agent (B) and copolymerizability with other monomers, a (meth)acrylic acid hydroxyalkyl ester having a hydroxyalkyl group having 1 to 4 carbon atoms is preferred. Specifically, for example, 2-hydroxyethyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, and the like are preferably used. These may be used alone or in combination of two or more.

[0041] Examples of the carboxyl group-containing monomer include ethylenically unsaturated carboxylic acids such as acrylic acid, methacrylic acid, crotonic acid, maleic acid, itaconic acid, and citraconic acid. Among them, acrylic acid is preferred in terms of the reactivity of the carboxyl group in the resulting (meth)acrylic acid ester polymer (A) with the crosslinking agent (B) and copolymerizability with other monomers. These may be used alone or in combination of two or more.

[0042] Examples of the amino group-containing monomer include aminoethyl (meth)acrylate and n-butylaminoethyl (meth)acrylate. These may be used alone or in combination of two or more. The amino group-containing monomer excludes the nitrogen atom-containing monomer described below.

[0043] The (meth)acrylic acid ester polymer (A) preferably contains reactive group-containing monomers as monomer units constituting the polymer in an amount of 1% by mass or more as a lower limit, more preferably 7% by mass or more, particularly preferably 13% by mass or more, further preferably 22% by mass or more, and most preferably 26% by mass or more. The (meth)acrylic acid ester polymer (A) preferably contains reactive group-containing monomers as monomer units constituting the polymer in an amount of 45% by mass or less as an upper limit, more preferably 40% by mass or less, particularly preferably 35% by mass or less, and further preferably 30% by mass or less. When the (meth)acrylic acid ester polymer (A) contains reactive group-containing monomers as monomer units in the above amount, a good crosslinked structure is formed in the obtained pressure-sensitive adhesive, and it becomes easy to set the dynamic hardness and storage shear modulus G' in a preferred range. In addition, when the light-diffusing fine particles (C) are contained, the dispersibility of the light-diffusing fine particles (C) in the obtained pressure-sensitive adhesive tends to be good.

[0044] It is also preferable that the (meth)acrylic acid ester polymer (A) does not contain a carboxyl group-containing monomer as a monomer unit constituting the polymer. Since a carboxyl group is an acid component, by not containing a carboxyl group-containing monomer, even if the target to which the pressure-sensitive adhesive is applied has a material that is defective due to acid, such as a transparent conductive film or a metal film, such as tin-doped indium oxide (ITO), the defects (corrosion, resistance value change, etc.) caused by acid can be suppressed. However, it is acceptable to contain a predetermined amount of a carboxyl group-containing monomer to the extent that such defects do not occur. Specifically, it is acceptable to contain a carboxyl group-containing monomer as a monomer unit in the (meth)acrylic acid ester polymer (A) in an amount of 0.1 mass% or less, preferably 0.01 mass% or less, and more preferably 0.001 mass% or less.

[0045] The (meth)acrylic acid ester polymer (A) preferably contains a (meth)acrylic acid alkyl ester as a monomer unit constituting the polymer. This allows the polymer to exhibit good adhesion. The alkyl group may be linear or branched.

[0046] As the (meth)acrylic acid alkyl ester, from the viewpoint of adhesion, the (meth)acrylic acid alkyl ester having an alkyl group with a carbon number of 1 to 20 is preferable. As the (meth)acrylic acid alkyl ester having an alkyl group with a carbon number of 1 to 20, for example, methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, n-butyl (meth)acrylate, n-pentyl (meth)acrylate, n-hexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isooctyl (meth)acrylate, n-decyl (meth)acrylate, n-dodecyl (meth)acrylate, myristyl (meth)acrylate, palmityl (meth)acrylate, stearyl (meth)acrylate, etc. are mentioned. Among them, from the viewpoint of further improving adhesion, the (meth)acrylic acid ester having an alkyl group with a carbon number of 4 to 8 is preferable, and n-butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, or isooctyl (meth)acrylate is particularly preferable. These may be used alone or in combination of two or more.

[0047] The (meth)acrylic acid ester polymer (A) preferably contains 20% by mass or more of (meth)acrylic acid alkyl ester as a monomer unit constituting the polymer, more preferably contains 30% by mass or more, particularly preferably contains 40% by mass or more, and even more preferably contains 45% by mass or more. When the lower limit of the content of the (meth)acrylic acid alkyl ester is as above, the (meth)acrylic acid ester polymer (A) can exhibit suitable adhesiveness. In addition, when the light diffusing fine particles (C) are contained, there is a tendency that the dispersibility of the light diffusing fine particles (C) in the adhesive can be improved, and the (meth)acrylic acid ester polymer (A) is prevented from losing the desired adhesiveness. On the other hand, the (meth)acrylic acid ester polymer (A) preferably contains 90% by mass or less of (meth)acrylic acid alkyl ester as a monomer unit constituting the polymer, more preferably contains 80% by mass or less, particularly preferably contains 70% by mass or less, and even more preferably contains 60% by mass or less. When the upper limit of the content of the (meth)acrylic acid alkyl ester is within the above range, a suitable amount of other monomer components such as a reactive functional group-containing monomer can be introduced into the (meth)acrylic acid ester polymer (A).

[0048] The (meth)acrylic acid ester polymer (A) preferably contains a monomer having an alicyclic structure in the molecule (alicyclic structure-containing monomer) as a monomer unit constituting the polymer. The alicyclic structure-containing monomer increases the glass transition temperature of the polymer, and increases the dynamic hardness and storage shear modulus G' of the resulting adhesive. In addition, since the alicyclic structure-containing monomer is bulky, it is presumed that the presence of this in the polymer increases the spacing between the polymers, thereby reducing the viscosity of the coating liquid and facilitating the thickening of the adhesive layer.

[0049] The carbon ring of the alicyclic structure in the alicyclic structure-containing monomer may be a saturated structure or may have an unsaturated bond in a part thereof. The alicyclic structure may be a monocyclic alicyclic structure or a polycyclic alicyclic structure. From the above viewpoint, a polycyclic alicyclic structure (polycyclic structure) is preferable, and a bicyclic to tetracyclic polycyclic structure is particularly preferable. From the above viewpoint, the carbon number of the alicyclic structure (meaning the total carbon number of the portion forming the ring, and when a plurality of rings are present independently, means the total carbon number) is preferably 5 to 15, and particularly preferably 7 to 10.

[0050] Specific examples of the alicyclic structure-containing monomer include cyclohexyl (meth)acrylate, dicyclopentanyl (meth)acrylate, adamantyl (meth)acrylate, isobornyl (meth)acrylate, dicyclopentenyl (meth)acrylate, dicyclopentenyloxyethyl (meth)acrylate, etc., among which, dicyclopentanyl (meth)acrylate (alicyclic structure carbon number: 10), adamantyl (meth)acrylate (alicyclic structure carbon number: 10) or isobornyl (meth)acrylate (alicyclic structure carbon number: 7) that exhibits better durability is preferred, and isobornyl (meth)acrylate is particularly preferred. These may be used alone or in combination of two or more.

[0051] When the (meth)acrylic acid ester polymer (A) contains an alicyclic structure-containing monomer as a monomer unit constituting the polymer, it is preferable that the alicyclic structure-containing monomer is contained in an amount of 1% by mass or more, particularly preferably 5% by mass or more, and more preferably 7% by mass or more. In addition, the content of the alicyclic structure-containing monomer is preferably 20% by mass or less, particularly preferably 15% by mass or less, and more preferably 10% by mass or less. By the content of the alicyclic structure-containing monomer being within the above range, it becomes easy to adjust the dynamic hardness and storage shear modulus G' to a preferred range.

[0052] The (meth)acrylic acid ester polymer (A) also preferably contains a nitrogen atom-containing monomer as a monomer unit constituting the polymer. By making the nitrogen atom-containing monomer exist as a constituent unit in the polymer, a predetermined polarity is imparted to the adhesive, and it can be made to have excellent affinity even for an adherend having a certain degree of polarity such as glass. As the nitrogen atom-containing monomer, from the viewpoint of imparting an appropriate rigidity to the (meth)acrylic acid ester polymer (A), a monomer having a nitrogen-containing heterocycle is preferable. In addition, from the viewpoint of increasing the degree of freedom of the portion derived from the nitrogen atom-containing monomer in the higher-order structure of the adhesive that is constituted, it is preferable that the nitrogen atom-containing monomer does not contain a reactive unsaturated double bond group other than one polymerizable group used in polymerization to form the (meth)acrylic acid ester polymer (A).

[0053] Examples of monomers having nitrogen-containing heterocycles include N-(meth)acryloylmorpholine, N-vinyl-2-pyrrolidone, N-(meth)acryloylpyrrolidone, N-(meth)acryloylpiperidine, N-(meth)acryloylpyrrolidine, N-(meth)acryloylaziridine, aziridinylethyl (meth)acrylate, 2-vinylpyridine, 4-vinylpyridine, 2-vinylpyrazine, 1-vinylimidazole, N-vinylcarbazole, and N-vinylphthalimide. Among these, N-(meth)acryloylmorpholine, which exhibits superior adhesion, is preferred. These may be used alone or in combination of two or more.

[0054] When the (meth)acrylic acid ester polymer (A) contains a nitrogen atom-containing monomer as a monomer unit constituting the polymer, it is preferable that the nitrogen atom-containing monomer is contained in an amount of 1% by mass or more, particularly preferably 3% by mass or more, and more preferably 5% by mass or more. In addition, the (meth)acrylic acid ester polymer (A) preferably contains a nitrogen atom-containing monomer as a monomer unit constituting the polymer in an amount of 20% by mass or less, particularly preferably 15% by mass or less, and more preferably 10% by mass or less. When the content of the nitrogen atom-containing monomer is within the above range, the obtained pressure-sensitive adhesive can fully exhibit excellent adhesive strength to glass.

[0055] The (meth)acrylic acid ester polymer (A) may contain other monomers as monomer units constituting the polymer, if desired. As the other monomers, monomers not containing reactive functional groups are preferred so as not to inhibit the above-mentioned action of the reactive functional group-containing monomer. Examples of such monomers include (meth)acrylic acid alkoxyalkyl esters such as methoxyethyl (meth)acrylate and ethoxyethyl (meth)acrylate, vinyl acetate, and styrene. These may be used alone or in combination of two or more.

[0056] The (meth)acrylic acid ester polymer (A) is preferably a linear polymer, which is likely to facilitate entanglement of molecular chains and is expected to improve cohesive strength, making it easier to obtain a pressure-sensitive adhesive with excellent durability under high temperature and high humidity conditions.

[0057] In addition, the (meth)acrylic acid ester polymer (A) is preferably a solution polymer obtained by a solution polymerization method. By using a solution polymer, a high molecular weight polymer can be easily obtained, and an improvement in cohesive strength can be expected, so that a pressure-sensitive adhesive having excellent durability under high temperature and high humidity conditions can be easily obtained.

[0058] The polymerization mode of the (meth)acrylic acid ester polymer (A) may be a random copolymer or a block copolymer.

[0059] The weight average molecular weight of the (meth)acrylic acid ester polymer (A) is preferably 200,000 or more, more preferably 300,000 or more, particularly preferably 400,000 or more, and even more preferably 500,000 or more, which can increase the dynamic hardness and storage shear modulus G' of the resulting pressure-sensitive adhesive.

[0060] The upper limit of the weight average molecular weight of the (meth)acrylic acid ester polymer (A) is preferably 1.5 million or less, more preferably 1.2 million or less, particularly preferably 1 million or less, and even more preferably 800,000 or less. When the upper limit of the weight average molecular weight of the (meth)acrylic acid ester polymer (A) is as above, the dynamic hardness and storage shear modulus G' of the resulting pressure-sensitive adhesive can be reduced, and the pressure-sensitive adhesive layer can be easily thickened. The weight average molecular weight in this specification is a value measured by gel permeation chromatography (GPC) in terms of standard polystyrene.

[0061] In the pressure-sensitive adhesive composition P, the (meth)acrylic acid ester polymer (A) may be used alone or in combination of two or more kinds.

[0062] (1-2) Crosslinking agent (B) The crosslinking agent (B) may be any that reacts with the reactive group of the (meth)acrylic acid ester polymer (A), and examples thereof include isocyanate-based crosslinking agents, epoxy-based crosslinking agents, amine-based crosslinking agents, melamine-based crosslinking agents, aziridine-based crosslinking agents, hydrazine-based crosslinking agents, aldehyde-based crosslinking agents, oxazoline-based crosslinking agents, metal alkoxide-based crosslinking agents, metal chelate-based crosslinking agents, metal salt-based crosslinking agents, and ammonium salt-based crosslinking agents. Among the above, it is preferable to use an isocyanate-based crosslinking agent that has excellent reactivity with hydroxyl groups and carboxy groups, or an epoxy-based crosslinking agent that has excellent reactivity with carboxy groups. The crosslinking agent (B) may be used alone or in combination of two or more.

[0063] The isocyanate-based crosslinking agent contains at least a polyisocyanate compound. Examples of the polyisocyanate compound include aromatic polyisocyanates such as tolylene diisocyanate, diphenylmethane diisocyanate, and xylylene diisocyanate, aliphatic polyisocyanates such as hexamethylene diisocyanate, alicyclic polyisocyanates such as isophorone diisocyanate and hydrogenated diphenylmethane diisocyanate, and their biuret and isocyanurate forms, as well as adducts which are reactants with low-molecular active hydrogen-containing compounds such as ethylene glycol, propylene glycol, neopentyl glycol, trimethylolpropane, and castor oil. Among these, trimethylolpropane-modified aromatic polyisocyanates, particularly trimethylolpropane-modified tolylene diisocyanate and trimethylolpropane-modified xylylene diisocyanate, are preferred from the viewpoint of reactivity with hydroxyl groups.

[0064] Examples of epoxy crosslinking agents include 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane, N,N,N',N'-tetraglycidyl-m-xylylenediamine, ethylene glycol diglycidyl ether, 1,6-hexanediol diglycidyl ether, trimethylolpropane diglycidyl ether, diglycidylaniline, diglycidylamine, etc. Among these, 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane is preferred from the viewpoint of reactivity with a carboxy group.

[0065] The content of the crosslinking agent (B) in the pressure-sensitive adhesive composition P is preferably 0.01 parts by mass or more, more preferably 0.05 parts by mass or more, and even more preferably 0.1 parts by mass or more, based on 100 parts by mass of the (meth)acrylic acid ester polymer (A). The content is preferably 10 parts by mass or less, more preferably 5 parts by mass or less, more preferably 1 part by mass or less, and even more preferably 0.4 parts by mass or less. When the content of the crosslinking agent (B) is within the above range, the above-mentioned physical properties and adhesive strength of the obtained pressure-sensitive adhesive tend to be favorable.

[0066] (1-3) Light diffusing particles (C) The light diffusing fine particles (C) may be any as long as the composite pressure-sensitive adhesive layer 2 having the obtained light diffusing pressure-sensitive adhesive layer 21 satisfies the above-mentioned haze value.

[0067] Examples of the light-diffusing fine particles include inorganic fine particles such as silica, calcium carbonate, aluminum hydroxide, magnesium hydroxide, clay, talc, and titanium dioxide; organic light-transmitting fine particles such as acrylic resin, polystyrene resin, polyethylene resin, and epoxy resin; and fine particles made of silicon-containing compounds having an intermediate structure between inorganic and organic, such as silicone resin (for example, Tospearl series manufactured by Momentive Performance Materials Japan). Among them, acrylic resin fine particles and fine particles made of silicon-containing compounds having an intermediate structure between inorganic and organic are preferred from the viewpoint of high-definition of the adhesive layer. In addition, fine particles made of silicon-containing compounds having an intermediate structure between inorganic and organic are particularly preferred because they exert their effect even with a small amount of addition and maintain good adhesion. The above light-diffusing fine particles may be used alone or in combination of two or more.

[0068] Examples of the acrylic resin fine particles include homopolymers of methyl methacrylate and copolymers of methyl methacrylate with monomers such as vinyl acetate, styrene, methyl acrylate, and ethyl acrylate.

[0069] The shape of the light diffusing microparticles is preferably spherical microparticles with uniform light diffusion. The average particle size of the light diffusing microparticles measured by centrifugal sedimentation light transmission method is preferably 1.0 μm or more as the lower limit, more preferably 2.0 μm or more, particularly preferably 3.0 μm or more, and even more preferably 4.0 μm or more. On the other hand, the upper limit is preferably 10.0 μm or less, particularly preferably 7.0 μm or less, and even more preferably 5.0 μm or less. By being within the above average particle size range, the obtained pressure sensitive adhesive can easily obtain a haze value in the above range while satisfying high total light transmittance.

[0070] The average particle size measured by the centrifugal sedimentation light transmission method was measured using a centrifugal automatic particle size distribution measuring device (Horiba, Ltd., CAPA-700) using a measurement sample prepared by thoroughly mixing 1.2 g of microparticles and 98.8 g of isopropyl alcohol.

[0071] The content of the light diffusing microparticles in the adhesive composition P is preferably 1 part by mass or more, more preferably 3 parts by mass or more, particularly preferably 8 parts by mass or more, and even more preferably 12 parts by mass or more, relative to 100 parts by mass of the (meth)acrylic acid ester polymer (A). The content of the light diffusing microparticles is preferably 50 parts by mass or less, particularly preferably 40 parts by mass or less, and even more preferably 30 parts by mass or less, relative to 100 parts by mass of the (meth)acrylic acid ester polymer (A). When the content of the light diffusing microparticles is within the above range, the composite pressure-sensitive adhesive layer 2 having the obtained light diffusing pressure-sensitive adhesive layer 21 easily satisfies the above-mentioned haze value, and also easily satisfies the above-mentioned dynamic hardness and storage shear modulus G'.

[0072] (1-4) Various additives If desired, various additives that are commonly used in acrylic adhesives, such as a silane coupling agent, an antirust agent, an ultraviolet absorber, an antistatic agent, a tackifier, an antioxidant, a light stabilizer, a softener, a refractive index adjuster, etc., can be added to the adhesive composition P. Note that polymerization solvents and dilution solvents described below are not included in the additives that constitute the adhesive composition P.

[0073] Among the above, it is preferable that the adhesive composition P contains a silane coupling agent, which improves adhesion to the adherend, whether the adherend is a plastic plate or a glass member, and provides the above-mentioned durability.

[0074] The silane coupling agent is preferably an organosilicon compound having at least one alkoxysilyl group in the molecule, which has good compatibility with the (meth)acrylic acid ester polymer (A) and has optical transparency.

[0075] Examples of such silane coupling agents include polymerizable unsaturated group-containing silicon compounds such as vinyltrimethoxysilane, vinyltriethoxysilane, and methacryloxypropyltrimethoxysilane; epoxy structure-containing silicon compounds such as 3-glycidoxypropyltrimethoxysilane and 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane; mercapto group-containing silicon compounds such as 3-mercaptopropyltrimethoxysilane, 3-mercaptopropyltriethoxysilane, and 3-mercaptopropyldimethoxymethylsilane. , 3-aminopropyltrimethoxysilane, N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane, and other amino group-containing silicon compounds, 3-chloropropyltrimethoxysilane, 3-isocyanatepropyltriethoxysilane, and condensates of at least one of these with alkyl group-containing silicon compounds such as methyltriethoxysilane, ethyltriethoxysilane, methyltrimethoxysilane, and ethyltrimethoxysilane. These may be used alone or in combination of two or more.

[0076] The content of the silane coupling agent in the adhesive composition P is preferably 0.01 parts by mass or more, more preferably 0.05 parts by mass or more, and even more preferably 0.1 parts by mass or more, based on 100 parts by mass of the (meth)acrylic acid ester polymer (A). The content is preferably 1.2 parts by mass or less, more preferably 0.8 parts by mass or less, and even more preferably 0.4 parts by mass or less.

[0077] (2) Preparation of adhesive composition The adhesive composition P can be produced by producing a (meth)acrylic acid ester polymer (A), mixing the (meth)acrylic acid ester polymer (A) with a crosslinking agent (B), and adding additives, etc., as desired. In the case of the light-diffusing adhesive layer 21, light-diffusing fine particles (C) are further blended.

[0078] The (meth)acrylic acid ester polymer (A) can be produced by polymerizing a mixture of monomers constituting the polymer by a normal radical polymerization method. The polymerization of the (meth)acrylic acid ester polymer (A) is preferably carried out by a solution polymerization method using a polymerization initiator as desired. However, the present invention is not limited thereto, and the polymerization may be carried out without a solvent. Examples of the polymerization solvent include ethyl acetate, n-butyl acetate, isobutyl acetate, toluene, acetone, hexane, methyl ethyl ketone, etc., and two or more of them may be used in combination.

[0079] Examples of the polymerization initiator include azo compounds and organic peroxides, and two or more of them may be used in combination. Examples of the azo compounds include 2,2'-azobisisobutyronitrile, 2,2'-azobis(2-methylbutyronitrile), 1,1'-azobis(cyclohexane 1-carbonitrile), 2,2'-azobis(2,4-dimethylvaleronitrile), 2,2'-azobis(2,4-dimethyl-4-methoxyvaleronitrile), dimethyl 2,2'-azobis(2-methylpropionate), 4,4'-azobis(4-cyanovaleric acid), 2,2'-azobis(2-hydroxymethylpropionitrile), and 2,2'-azobis[2-(2-imidazolin-2-yl)propane].

[0080] Examples of organic peroxides include benzoyl peroxide, t-butyl perbenzoate, cumene hydroperoxide, diisopropyl peroxydicarbonate, di-n-propyl peroxydicarbonate, di(2-ethoxyethyl)peroxydicarbonate, t-butyl peroxyneodecanoate, t-butyl peroxypivalate, (3,5,5-trimethylhexanoyl)peroxide, dipropionyl peroxide, and diacetyl peroxide.

[0081] In the above polymerization step, the weight average molecular weight of the resulting polymer can be adjusted by adding a chain transfer agent such as 2-mercaptoethanol.

[0082] After the (meth)acrylic acid ester polymer (A) is obtained, the crosslinking agent (B), and optionally the dilution solvent, the light-diffusing fine particles (C), the additives, etc. are added to the solution of the (meth)acrylic acid ester polymer (A) and mixed thoroughly to obtain a solvent-diluted adhesive composition P (coating solution). When any of the above components is in a solid state or when precipitation occurs when mixed with other components in an undiluted state, the component may be dissolved or diluted alone in a dilution solvent before mixing with other components.

[0083] Examples of the dilution solvent include aliphatic hydrocarbons such as hexane, heptane, and cyclohexane; aromatic hydrocarbons such as toluene and xylene; halogenated hydrocarbons such as methylene chloride and ethylene chloride; alcohols such as methanol, ethanol, propanol, butanol, and 1-methoxy-2-propanol; ketones such as acetone, methyl ethyl ketone, 2-pentanone, isophorone, and cyclohexanone; esters such as ethyl acetate and butyl acetate; and cellosolve-based solvents such as ethyl cellosolve.

[0084] The concentration and viscosity of the coating solution thus prepared are not particularly limited as long as they are within the range that allows coating, and can be appropriately selected according to the situation. For example, the adhesive composition P is diluted so that the concentration becomes 10 to 60 mass %. In addition, when obtaining the coating solution, the addition of a dilution solvent or the like is not a necessary condition, and if the adhesive composition P has a viscosity that allows coating, it is not necessary to add a dilution solvent. In this case, the adhesive composition P becomes a coating solution in which the polymerization solvent of the (meth)acrylic acid ester polymer (A) itself serves as the dilution solvent.

[0085] (3) Formation of adhesive layer In this embodiment, the light diffusing adhesive layer 21 and the transparent adhesive layer 22 are preferably each made of an adhesive obtained by crosslinking (a coating layer of) an adhesive composition P. Crosslinking of the adhesive composition P can usually be carried out by a heat treatment. This heat treatment can also serve as a drying treatment for volatilizing a diluting solvent and the like from the coating layer of the adhesive composition P applied to a desired object.

[0086] The heating temperature in the heat treatment is preferably 50 to 150° C., and more preferably 70 to 120° C. The heating time is preferably 10 seconds to 10 minutes, and more preferably 50 seconds to 2 minutes.

[0087] After the heat treatment, a curing period of about 1 to 2 weeks may be provided at room temperature (e.g., 23°C, 50% RH) as necessary. If this curing period is required, the adhesive is formed after the curing period has elapsed, and if no curing period is required, the adhesive is formed after the heat treatment is completed.

[0088] By the above heat treatment (and curing), the (meth)acrylic acid ester polymer (A) is sufficiently crosslinked via the crosslinking agent (B).

[0089] The composite pressure-sensitive adhesive layer 2 in this embodiment can be obtained by laminating a light diffusing pressure-sensitive adhesive layer 21 and a transparent pressure-sensitive adhesive layer 22. The lamination may be performed before or after each pressure-sensitive adhesive layer is cured. However, in order to enhance the adhesion between the light diffusing pressure-sensitive adhesive layer 21 and the transparent pressure-sensitive adhesive layer 22, it is preferable to laminate the pressure-sensitive adhesive layers before curing them.

[0090] (4) Thickness of the adhesive layer The total thickness of the composite pressure-sensitive adhesive layer 2, in this embodiment, the total thickness of the light-diffusing pressure-sensitive adhesive layer 21 and the transparent pressure-sensitive adhesive layer 22, is preferably 70 μm or more as a lower limit, particularly preferably 110 μm or more, and more preferably 140 μm or more. By setting the lower limit of the total thickness of the composite pressure-sensitive adhesive layer 2 as above, it becomes easier to satisfy the above-mentioned haze value, and it becomes easier to relax the stress of the pressure-sensitive adhesive layer against the compression of the liquid crystal cell, which is two hard plates, and the prevention of image display unevenness is further improved. On the other hand, the total thickness of the composite pressure-sensitive adhesive layer 2 is preferably 3000 μm or less as an upper limit, particularly preferably 1000 μm or less, more preferably 500 μm or less, and most preferably 420 μm or less. By setting the upper limit of the total thickness of the composite pressure-sensitive adhesive layer 2 as above, it is possible to prevent image blurring and a decrease in total light transmittance.

[0091] The thickness of the light diffusing pressure-sensitive adhesive layer 21 has a lower limit of preferably 10 μm or more, more preferably 20 μm or more, and even more preferably 40 μm or more. When the lower limit of the thickness of the light diffusing pressure-sensitive adhesive layer 21 is as described above, it becomes easier to satisfy the above-mentioned haze value. On the other hand, the upper limit of the thickness of the light diffusing pressure-sensitive adhesive layer 21 is preferably 300 μm or less, more preferably 100 μm or less, and even more preferably 80 μm or less. When the upper limit of the thickness of the light diffusing pressure-sensitive adhesive layer 21 is as described above, it is possible to prevent image blurring and a decrease in total light transmittance.

[0092] In addition, the thickness of the transparent adhesive layer 22 is preferably 20 μm or more as a lower limit, particularly preferably 40 μm or more, and more preferably 80 μm or more. By setting the lower limit of the thickness of the transparent adhesive layer 22 as above, it becomes easier to relax the stress of the adhesive layer against the compression of the liquid crystal cell, which is two hard plates, and the prevention of image display unevenness is further improved. On the other hand, the thickness of the transparent adhesive layer 22 is preferably 2700 μm or less as an upper limit, particularly preferably 900 μm or less, more preferably 420 μm or less, and most preferably 340 μm or less. By setting the upper limit of the thickness of the transparent adhesive layer 22 as above, it is possible to prevent image blurring and a decrease in total light transmittance.

[0093] 1-2.Release sheet The release sheets 3a and 3b protect the composite adhesive layer 2 until the adhesive sheet 1 is used, and are peeled off when the adhesive sheet 1 (composite adhesive layer 2) is used. In the adhesive sheet 1 according to this embodiment, one or both of the release sheets 3a and 3b are not necessarily required.

[0094] Examples of the release sheets 3a and 3b include polyethylene films, polypropylene films, polybutene films, polybutadiene films, polymethylpentene films, polyvinyl chloride films, vinyl chloride copolymer films, polyethylene terephthalate films, polyethylene naphthalate films, polybutylene terephthalate films, polyurethane films, ethylene vinyl acetate films, ionomer resin films, ethylene-(meth)acrylic acid copolymer films, ethylene-(meth)acrylic acid ester copolymer films, polystyrene films, polycarbonate films, polyimide films, and fluororesin films. Crosslinked films of these films are also used. Furthermore, laminated films of these films may be used.

[0095] The release surfaces of the release sheets 3a and 3b (particularly the surfaces in contact with the composite pressure-sensitive adhesive layer 2) are preferably subjected to a release treatment. Examples of the release agent used for the release treatment include alkyd-based, silicone-based, fluorine-based, unsaturated polyester-based, polyolefin-based, and wax-based release agents.

[0096] Of the release sheets 3a and 3b, it is preferred that one of the release sheets is a heavy release type release sheet having a large release force and the other is a light release type release sheet having a small release force. For example, the release sheet 3a on the side in contact with the light diffusing adhesive layer 21 may be a light release type release sheet and the release sheet 3b on the side in contact with the transparent adhesive layer 22 may be a heavy release type release sheet, or the release sheet 3a on the side in contact with the light diffusing adhesive layer 21 may be a heavy release type release sheet and the release sheet 3b on the side in contact with the transparent adhesive layer 22 may be a light release type release sheet.

[0097] There is no particular limitation on the thickness of the release sheets 3a and 3b, but it is usually about 20 to 150 μm.

[0098] 2. Manufacturing of adhesive sheets In one example of manufacturing the adhesive sheet 1, a coating solution of the adhesive composition P for forming the transparent adhesive layer 22 is applied to the release surface of one release sheet 3a, and a heat treatment is performed to thermally crosslink the adhesive composition P to form a coating layer, thereby obtaining a release sheet 3a with a coating layer. Also, a coating solution of the adhesive composition P for forming the light diffusing adhesive layer 21 is applied to the release surface of the other release sheet 3b, and a heat treatment is performed to thermally crosslink the adhesive composition P to form a coating layer, thereby obtaining a release sheet 3b with a coating layer. Then, the release sheet 3a with the coating layer and the release sheet 3b with the coating layer are bonded together so that both coating layers come into contact with each other. Here, a plurality of release sheets with coating layers may be prepared, and the coating layers may be bonded together in a desired number of layers in a desired stacking order. If a curing period is required, a curing period is provided, and if a curing period is not required, the laminated coating layers are left as they are to become the composite adhesive layer 2. As a result, the above-mentioned adhesive sheet 1 having the composite adhesive layer 2, which is a laminate of the light diffusing adhesive layer 21 and the transparent adhesive layer 22, is obtained. The heat treatment and curing conditions are as described above.

[0099] In addition, the coating layer for forming the transparent adhesive layer 22 and the coating layer for forming the light diffusing adhesive layer 21 may each be sandwiched between two release sheets, and when the coating layer for forming the transparent adhesive layer 22 and the coating layer for forming the light diffusing adhesive layer 21 are bonded together, one of the release sheets may be peeled off.

[0100] The coating solution of the pressure-sensitive adhesive composition P can be applied by, for example, bar coating, knife coating, roll coating, blade coating, die coating, gravure coating, or the like.

[0101] 3. Physical properties (1) Adhesive strength From the viewpoint of durability, the adhesive strength of the transparent adhesive layer 22 side of the adhesive sheet 1 according to this embodiment to soda lime glass is preferably 1N / 25mm or more, more preferably 10N / 25mm or more, particularly preferably 30N / 25mm or more, and even more preferably 40N / 25mm or more. Moreover, the adhesive strength is preferably 80N / 25mm or less, more preferably 70N / 25mm or less, particularly preferably 60N / 25mm or less, and even more preferably 50N / 25mm or less. This provides good reworkability, and allows the adherend to be reused even if a lamination error occurs.

[0102] From the viewpoint of durability, the adhesive strength of the surface of the light diffusing adhesive layer 21 side of the adhesive sheet 1 according to this embodiment to soda lime glass is preferably 1N / 25mm or more, more preferably 10N / 25mm or more, particularly preferably 20N / 25mm or more, and even more preferably 30N / 25mm or more. Moreover, the adhesive strength is preferably 80N / 25mm or less, more preferably 60N / 25mm or less, particularly preferably 50N / 25mm or less, and even more preferably 40N / 25mm or less. This provides good reworkability, and allows the adherend to be reused even if a lamination error occurs.

[0103] Here, the adhesive strength in this specification basically refers to the adhesive strength measured by the 180-degree peeling method in accordance with JIS Z0237:2009, and the measurement sample is 25 mm wide and 100 mm long, and the measurement sample is attached to the adherend and pressurized at 0.5 MPa and 50°C for 20 minutes, and then left to stand for 24 hours under conditions of normal pressure, 23°C and 50% RH, and then measured at a peeling speed of 300 mm / min.

[0104] (2) Total light transmittance The total light transmittance of the composite pressure-sensitive adhesive layer 2 in the pressure-sensitive adhesive sheet 1 according to this embodiment is preferably 80% or more, more preferably 85% or more, and particularly preferably 90% or more. If the total light transmittance is within the above range, the transparency is very high, and the sheet is particularly suitable for optical applications (displays). The method for measuring the total light transmittance is as shown in the test examples described later.

[0105] 4. Other embodiments The adhesive sheet according to the present embodiment has a composite adhesive layer including a light-diffusing adhesive layer containing light-diffusing microparticles and a transparent adhesive layer not containing light-diffusing microparticles, and the transparent adhesive layer has a storage shear modulus G' of 0.07 MPa or more and 10 MPa or less, and the composite adhesive layer has a haze value of 70% or more and 99% or less. When such an adhesive sheet is used to bond two liquid crystal cells, moire and image display unevenness are unlikely to occur, as in the above-mentioned embodiment. In addition, the durability is excellent under high temperature and high humidity conditions, particularly due to the action of the storage shear modulus G'.

[0106] In the pressure-sensitive adhesive sheet according to the above-mentioned embodiment, the physical properties of the pressure-sensitive adhesive layer are defined by the dynamic hardness, which represents the local elastic behavior from the surface of the pressure-sensitive adhesive layer to the thickness direction of the pressure-sensitive adhesive layer. In contrast, in the pressure-sensitive adhesive sheet according to the present embodiment, the physical properties of each of the light-diffusing pressure-sensitive adhesive layer and the transparent pressure-sensitive adhesive layer are defined by the storage shear modulus G', which represents the overall elastic behavior of each layer. This also provides excellent durability, as with the pressure-sensitive adhesive sheet according to the above-mentioned embodiment, and can suppress unevenness in the displayed image when liquid crystal cells are bonded together.

[0107] From the viewpoint of durability, the storage shear modulus G' of the transparent adhesive layer is preferably 0.10 MPa or more, more preferably 0.13 MPa or more, particularly preferably 0.17 MPa or more, and even more preferably 0.20 MPa or more. From the viewpoint of preventing display unevenness, the storage shear modulus G' of the transparent adhesive layer is preferably 5 MPa or less, more preferably 1 MPa or less, particularly preferably 0.7 MPa or less, and even more preferably 0.4 MPa or less.

[0108] The storage shear modulus G' of the light diffusion pressure-sensitive adhesive layer is preferably 0.07 MPa or more, more preferably 0.08 MPa or more, particularly preferably 0.09 MPa or more, and even more preferably 0.10 MPa or more. This makes the above-mentioned durability more excellent. In addition, from the viewpoint of preventing display unevenness, the storage shear modulus G' of the light diffusion pressure-sensitive adhesive layer is preferably 10 MPa or less, more preferably 5 MPa or less, particularly preferably 0.7 MPa or less, and even more preferably 0.4 MPa or less.

[0109] The thickness of each layer and the composite pressure-sensitive adhesive layer, and the physical properties other than the dynamic hardness are the same as those of the above-mentioned embodiment. The transparent pressure-sensitive adhesive layer and the light-diffusing pressure-sensitive adhesive layer having the above-mentioned physical properties can be preferably formed by the pressure-sensitive adhesive (pressure-sensitive adhesive composition P) described in the above-mentioned embodiment.

[0110] [Method for producing laminate] In one embodiment of the present invention, a laminate can be produced by laminating two hard plates with an adhesive layer using the adhesive sheet according to the above embodiment. In a method for producing a laminate according to one embodiment of the present invention, the light diffusing adhesive layer 21 of the composite adhesive layer 2 in the adhesive sheet 1 is laminated to one hard plate, and then the transparent adhesive layer 22 of the composite adhesive layer 2 is laminated to the other hard plate.

[0111] When two hard plates are bonded together with an adhesive layer, generally, a first hard plate is bonded to one side of the adhesive layer, and then a second hard plate is bonded to the other side of the adhesive layer. At this time, the second hard plate to be bonded later is pressed strongly against the adhesive layer so as not to trap air at the interface with the adhesive layer. In this case, the contact portion of the adhesive layer with the second hard plate, especially the contact portion that first comes into contact, is easily deformed, and if a light-diffusing adhesive layer is present at the contact portion, the dispersion state of the light-diffusing fine particles is easily disturbed, and the uniformity of light diffusion may decrease. However, as described above, if the light-diffusing adhesive layer is bonded to one (first) hard plate first, and then the transparent adhesive layer is bonded to the other (second) hard plate, the deformation of the light-diffusing adhesive layer can be suppressed and the uniformity of light diffusion can be well maintained. As a result, for example, when two liquid crystal cells are bonded together as a hard plate, the occurrence of moire can be uniformly suppressed, and the occurrence of unevenness in the displayed image can be more effectively suppressed.

[0112] In this specification, the term "hard plate" refers to a plate-like member having a hardness that is almost inflexible. Examples of such hard plates include glass plates, plastic plates, and those having various functional layers (transparent conductive films, metal layers, silica layers, hard coat layers, anti-glare layers, etc.), as well as display modules such as liquid crystal (LCD) modules (liquid crystal cells), light-emitting diode (LED) modules, and organic electroluminescence (OLED) modules, optical members as part of a display module, and laminates including a display module.

[0113] [Liquid crystal display components] A liquid crystal display member according to one embodiment of the present invention is configured to include a first liquid crystal cell, a second liquid crystal cell, and an adhesive layer that bonds them together. This adhesive layer is the composite adhesive layer of the adhesive sheet according to the embodiment described above. Due to the action of the composite adhesive layer, this liquid crystal display member is less likely to cause moire and image display unevenness, and also has excellent durability under high temperature and high humidity conditions.

[0114] A preferred example of the pressure-sensitive adhesive layer in this embodiment is a composite pressure-sensitive adhesive layer consisting of two layers, a light-diffusing pressure-sensitive adhesive layer and a transparent pressure-sensitive adhesive layer, which will be described below with reference to the drawings.

[0115] 2, the liquid crystal display member 4 according to this embodiment includes a first liquid crystal cell 5a, a second liquid crystal cell 5b, and a composite pressure-sensitive adhesive layer 2 that bonds them together. The composite pressure-sensitive adhesive layer 2 in this embodiment is composed of two layers: a light-diffusing pressure-sensitive adhesive layer 21 in contact with the first liquid crystal cell 5a, and a transparent pressure-sensitive adhesive layer 22 in contact with the second liquid crystal cell 5b.

[0116] The light diffusing adhesive layer 21 and the transparent adhesive layer 22 are the light diffusing adhesive layer 21 and the transparent adhesive layer 22 in the above-mentioned adhesive sheet 1, and the details of their configurations are as described above.

[0117] The first liquid crystal cell 5a and the second liquid crystal cell 5b are those that are commonly used in liquid crystal (LCD) displays, particularly liquid crystal displays that display stereoscopic images, and are not particularly limited. Note that the "liquid crystal cell" is also sometimes called a "liquid crystal panel," "liquid crystal module," "liquid crystal display element," etc.

[0118] The first liquid crystal cell 5a and the second liquid crystal cell 5b are usually hard plates, and their thickness is usually about 0.5 to 5.0 mm, and preferably about 1.0 to 3.0 mm.

[0119] A preferred method for producing the liquid crystal display member 4 will be described. However, the present invention is not limited to this. First, the release sheet 3a (preferably a light-release type release sheet) is peeled off from the adhesive sheet 1 to expose the light-diffusing adhesive layer 21, and the exposed light-diffusing adhesive layer 21 is attached to one side of the first liquid crystal cell 5a. At this time, the adhesive sheet 1 maintains a state in which the flexible release sheet 3b is attached to the side opposite to the side in contact with the liquid crystal cell 5a. Therefore, the stress unevenness of the light-diffusing adhesive layer 21 generated when the adhesive sheet 1 is attached to the liquid crystal cell 5a is immediately eliminated. In addition, when the adhesive sheet 1 is attached to the liquid crystal cell 5a, the transparent adhesive layer 22 plays the role of a cushioning material, and can suppress the application of excessive pressure to the liquid crystal cell 5a. These actions can prevent the alignment of the liquid crystal cell 5a, which causes image display unevenness when the liquid crystal display member 4 is formed, at this stage.

[0120] Next, the release sheet 3b (preferably a heavy release type release sheet) is peeled off from the adhesive sheet 1 (composite adhesive layer 2) attached to the first liquid crystal cell 5a to expose the transparent adhesive layer 22, and the second liquid crystal cell 5b is attached to the exposed transparent adhesive layer 22. Here, stress is generated in the composite adhesive layer 2 by bonding with the liquid crystal cell 5b. However, since the composite adhesive layer 2 has the transparent adhesive layer 22, the stress on the light diffusion adhesive layer 21 is relaxed, and the occurrence of stress unevenness due to the density of the light diffusion fine particles is prevented. In the liquid crystal display member 4 obtained in this manner, the alignment of the liquid crystal cells 5a, 5b is prevented from being disturbed due to the stress unevenness caused by the light diffusion adhesive layer 21 in the composite adhesive layer 2, and thus the occurrence of unevenness in the displayed image is suppressed, and the displayed image is displayed satisfactorily.

[0121] Alternatively, the release sheet 3b (preferably a light release type release sheet) may be first peeled off from the adhesive sheet 1, the transparent adhesive layer 22 and the second liquid crystal cell 5b may be bonded together, and then the release sheet 3a (preferably a heavy release type release sheet) may be peeled off, and the light diffusing adhesive layer 21 and the first liquid crystal cell 5a may be bonded together.

[0122] The above-described embodiments are described for the purpose of facilitating understanding of the present invention, and are not described for the purpose of limiting the present invention. Therefore, each element disclosed in the above embodiment is intended to include all design modifications and equivalents that fall within the technical scope of the present invention.

[0123] For example, the composite pressure-sensitive adhesive layer 2 in the pressure-sensitive adhesive sheet 1 may have a structure of three or more layers. In addition, either one of the release sheets 3a, 3b in the pressure-sensitive adhesive sheet 1 may be omitted. EXAMPLES

[0124] The present invention will be described in more detail below with reference to examples, but the scope of the present invention is not limited to these examples.

[0125] [Production Example 1] (Preparation of Coating Layer with Release Sheet for Light Diffusing Adhesive Layer) 1. Preparation of (meth)acrylic acid ester polymers 25 parts by mass of n-butyl acrylate, 25 parts by mass of 2-ethylhexyl acrylate, 10 parts by mass of isobornyl acrylate, 10 parts by mass of N-acryloylmorpholine, and 30 parts by mass of 2-hydroxyethyl acrylate were copolymerized by solution polymerization to prepare a (meth)acrylic acid ester polymer (A). The molecular weight of this (meth)acrylic acid ester polymer (A) was measured by the method described below, and the weight average molecular weight (Mw) was 500,000.

[0126] 2. Preparation of adhesive composition 100 parts by mass (solid content equivalent; the same applies below) of the (meth)acrylic acid ester polymer (A) obtained in the above step 1, 0.2 parts by mass of trimethylolpropane-modified tolylene diisocyanate (manufactured by Toyochem Co., Ltd., product name "BHS8515") as a crosslinking agent (B), 15 parts by mass of fine particles (manufactured by Momentive Performance Materials Japan, Inc., product name "Tospearl 145", average particle size: 4.5 μm) made of silicone resin (a silicon-containing compound having an intermediate structure between inorganic and organic) as light-diffusing fine particles (C), and 0.3 parts by mass of 3-glycidoxypropyltrimethoxysilane as a silane coupling agent were mixed, thoroughly stirred, and diluted with methyl ethyl ketone to obtain a coating solution of an adhesive composition.

[0127] Here, the formulations (solid content equivalent) of the pressure-sensitive adhesive composition when the (meth)acrylic acid ester polymer (A) is taken as 100 parts by mass (solid content equivalent) are shown in Table 1. The details of the abbreviations and the like shown in Table 1 are as follows. [(Meth)acrylic acid ester polymer (A)] BA: n-butyl acrylate 2EHA: 2-ethylhexyl acrylate IBXA: Isobornyl acrylate ACMO: N-Acryloylmorpholine HEA: 2-hydroxyethyl acrylate AA: Acrylic acid [Crosslinking agent (B)] TDI: Trimethylolpropane modified tolylene diisocyanate (manufactured by Toyochem Co., Ltd., product name "BHS8515") XDI: Trimethylolpropane modified xylylene diisocyanate (manufactured by Soken Chemical Industries, Ltd., product name "TD-75") Epoxy: 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane (manufactured by Mitsubishi Gas Chemical Company, product name "TETRAD-C") [Light Diffusion Particles (C)] D1: Microparticles made of silicone resin (a silicon-containing compound with an intermediate structure between inorganic and organic) with an average particle size of 4.5 μm (manufactured by Momentive Performance Materials Japan, product name "Tospearl 145", refractive index: 1.43) D2: Spherical polymethylmethacrylate-polystyrene copolymer microparticles with an average particle size of 5.0 μm (manufactured by Sekisui Chemical Co., Ltd., product name "XX-23LA", refractive index: 1.525)

[0128] 3. Formation of coating layer The coating solution of the adhesive composition obtained in the above step 2 was applied by a knife coater to the release-treated surface of a light-release type release sheet (manufactured by Lintec Corporation, product name "SP-PET381031"), one side of which was treated for release with a silicone-based release agent, and then heated at 90°C for 1 minute to form a coating layer (thickness: 50 μm). This resulted in a coating layer with a release sheet consisting of a coating layer (thickness: 50 μm) of a light-release type release sheet / light-diffusing adhesive layer. In addition, for test examples, the coating layer with the release sheet was aged for 7 days under conditions of 23°C and 50% RH to obtain a light-diffusing adhesive layer with a release sheet.

[0129] The thickness of the coating layer is a value measured using a constant pressure thickness measuring instrument (manufactured by Techclock Corporation, product name "PG-02") in accordance with JIS K7130 (the same applies below).

[0130] [Production Examples 2 to 7] (Preparation of Coating Layer with Release Sheet for Light Diffusing Pressure Sensitive Adhesive Layer) A coating layer with a release sheet for the light-diffusing adhesive layer and a light-diffusing adhesive layer with a release sheet were prepared in the same manner as in Production Example 1, except that the types and ratios of the monomers constituting the (meth)acrylic acid ester polymer (A), the weight-average molecular weight (Mw) of the (meth)acrylic acid ester polymer (A), the type and amount of the crosslinking agent (B), the type and amount of the light-diffusing microparticles (C), and the amount of the silane coupling agent were changed as shown in Table 1.

[0131] [Production Example 8] (Preparation of Coating Layer with Release Sheet for Light Diffusing Adhesive Layer) The types and ratios of the monomers constituting the (meth)acrylic acid ester polymer (A) were changed as shown in Table 1, and 5.5 parts by mass of ε-caprolactone-modified tris-(2-acryloxyethyl)isocyanurate (manufactured by Shin-Nakamura Chemical Co., Ltd., product name "NK Ester A-9300-1CL") as an active energy ray curable component and 0.5 parts by mass of 2,4,6-trimethylbenzoyl-diphenyl-phosphine oxide as a photopolymerization initiator were further added, and a coating layer with a release sheet for a light-diffusing adhesive layer and a light-diffusing adhesive layer with a release sheet were prepared in the same manner as in Production Example 1. The light-diffusing adhesive layer was made of an active energy ray curable adhesive.

[0132] [Production Examples 9 to 10] (Preparation of Coating Layer with Release Sheet for Transparent Adhesive Layer) The types and ratios of the monomers constituting the (meth)acrylic acid ester polymer (A) and the amount of light-diffusing microparticles (C) (not blended) were changed as shown in Table 1, and a coating layer with a release sheet and a transparent adhesive layer with a release sheet were prepared in the same manner as in Production Example 1, except that the coating layer was coated on the release-treated surface of a heavy release type release sheet (manufactured by Lintec Corporation, product name "SP-PET752150") instead of a light release type release sheet.

[0133] The weight average molecular weight (Mw) mentioned above is a polystyrene-equivalent weight average molecular weight measured by gel permeation chromatography (GPC) under the following conditions (GPC measurement). <Measurement conditions> GPC measuring device: Tosoh HLC-8020 GPC columns (passed in the following order): Tosoh Corporation TSK guard column HXL-H TSK gel GMHXL (×2) TSK gel G2000HXL Measurement solvent: Tetrahydrofuran ·Measurement temperature: 40℃

[0134] Example 1 The coating layer for the light diffusing adhesive layer prepared in Production Example 1 and the coating layer for the transparent adhesive layer prepared in Production Example 9 were laminated together, and then aged for 7 days under conditions of 23° C. and 50% RH. In this manner, an adhesive sheet (light diffusing adhesive layer + transparent adhesive layer = composite adhesive layer) consisting of a light release type release sheet / light diffusing adhesive layer (50 μm) / transparent adhesive layer (50 μm) / heavy release type release sheet was produced.

[0135] [Examples 2 to 8, Comparative Examples 1 to 3] Adhesive sheets were produced in the same manner as in Example 1, except that the type of light diffusing adhesive layer (Production Examples 1 to 8) and the type of transparent adhesive layer (Production Examples 9 to 10), as well as the thickness and total thickness of the transparent adhesive layer, were changed as shown in Table 2. The thickness of the transparent adhesive layer was changed by laminating the desired number of coating layers (50 μm) of the transparent adhesive layer of the transparent adhesive sheet produced in each production example.

[0136] [Test Example 1] (Measurement of gel fraction) The light-diffusing adhesive layer with release sheet and the transparent adhesive layer with release sheet produced in each production example (except production example 8) were cut to a size of 80 mm x 80 mm. Each adhesive layer was wrapped in a polyester mesh (mesh size 200), and its mass was measured using a precision balance. The mass of the mesh alone was subtracted to calculate the mass of the adhesive alone. This mass was designated as M1.

[0137] Next, the adhesive wrapped in the polyester mesh was immersed in ethyl acetate at room temperature (23°C) for 24 hours. The adhesive was then removed and air-dried for 24 hours in an environment with a temperature of 23°C and a relative humidity of 50%, and then dried in an oven at 80°C for 12 hours. After drying, the mass was weighed using a precision balance, and the mass of the adhesive alone was calculated by subtracting the mass of the mesh alone. This mass was designated M2. The gel fraction (%) was expressed as (M2 / M1) x 100. The gel fraction of the adhesive was calculated from this. The results are shown in Table 2.

[0138] In addition, the light-diffusing adhesive layer prepared in Production Example 8 was irradiated with active energy rays (ultraviolet rays; UV) under the following conditions to cure the light-diffusing adhesive layer to form a cured adhesive layer. The gel fraction (after UV) of the adhesive of this cured adhesive layer was calculated in the same manner as above. The results are shown in Table 2.

[0139] <Activated energy ray irradiation conditions> -Uses high pressure mercury lamp ·Illuminance 200mW / cm 2 ,Light intensity 1000mJ / cm 2 The UV illuminance and light intensity meter used is the "UVPF-A1" manufactured by Eye Graphics.

[0140] [Test Example 2] (Measurement of dynamic hardness) The heavy release type release sheet was peeled off from the adhesive sheet produced in the examples and comparative examples (except Comparative Example 3), and the exposed transparent adhesive layer was attached and fixed to a glass plate. Next, the light release type release sheet was peeled off, and the exposed light diffusion adhesive layer was pressed into the light diffusion adhesive layer using a dynamic ultra-microhardness tester (manufactured by Shimadzu Corporation, product name "Shimadzu Dynamic Ultra-Microhardness Tester DUH-W201S") at a loading speed of 0.0142 mN / sec under an environment of 23°C, until the depth reached 4 μm or the test force reached 1 mN, and the pressing depth D (μm) and the test force P (mN) were read, and the dynamic hardness (DHT115-1) was calculated by the following formula. Dynamic hardness (DHT115-1) = 3.8584 x P / D 2 (where 3.8584 is a constant determined by the shape of the indenter.)

[0141] In addition, the light release type release sheet was peeled off from the pressure-sensitive adhesive sheets produced in the Examples and Comparative Examples (except Comparative Example 3), and the exposed light-diffusing pressure-sensitive adhesive layer was attached and fixed to a glass plate. Next, the heavy release type release sheet was peeled off, and the exposed transparent pressure-sensitive adhesive layer was tested in the same manner as above to determine the dynamic hardness (DHT115-1).

[0142] On the other hand, the heavy release type release sheet was peeled off from the pressure sensitive adhesive sheet produced in Comparative Example 3, and the exposed transparent pressure sensitive adhesive layer was attached and fixed to a glass plate. Next, active energy rays (ultraviolet rays; UV) were irradiated through the light release type release sheet under the same conditions as in Test Example 1 to cure the composite pressure sensitive adhesive layer. Then, the light release type release sheet was peeled off, and the exposed light diffusing pressure sensitive adhesive layer after curing with active energy rays was tested in the same manner as above to determine the dynamic hardness (DHT115-1; after UV). In addition, the transparent pressure sensitive adhesive layer after curing with active energy rays was also tested in the same manner as above to determine the dynamic hardness (DHT115-1; after UV). The respective results are shown in Table 2.

[0143] [Test Example 3] (Measurement of storage shear modulus G') The light-diffusing adhesive layer and the transparent adhesive layer prepared in each Production Example (except Production Example 8) were laminated in multiple layers to form a laminate with a thickness of 800 μm. A cylindrical body with a diameter of 8 mm (height of 800 μm) was punched out from the obtained laminate of the adhesive layers to prepare a sample.

[0144] The storage shear modulus G' (MPa) of the above samples was measured under the following conditions by a torsional shear method using a viscoelasticity measuring device (manufactured by Anton Paar, product name "MCR301") in accordance with JIS K7244-1. The results are shown in Table 2. Measurement frequency: 1Hz Measurement temperature: 23℃

[0145] A cylinder was also obtained from the light-diffusing adhesive layer prepared in Production Example 8 in the same manner as above. This cylinder was irradiated with active energy rays (ultraviolet rays; UV) under the same conditions as in Test Example 1 to cure the active energy ray-curable adhesive, thereby obtaining a sample after active energy ray curing. The storage shear modulus G' (MPa; after UV) at 23°C was measured for the obtained sample after active energy ray curing in the same manner as above. The results are shown in Table 2.

[0146] [Test Example 4] (Haze value measurement) The composite adhesive layer of the adhesive sheet produced in the examples and comparative examples was attached to soda lime glass to prepare a measurement sample. After background measurement was performed on the soda lime glass, the haze value (%) of the measurement sample was measured using a haze meter (manufactured by Nippon Denshoku Industries Co., Ltd., product name "NDH5000") in accordance with JIS K7136:2000. The results are shown in Table 2.

[0147] [Test Example 5] (Measurement of total light transmittance) The composite adhesive layer of the adhesive sheet produced in the examples and comparative examples was attached to soda lime glass to prepare a measurement sample. After background measurement was performed on the soda lime glass, the total light transmittance (%) of the measurement sample was measured using a haze meter (manufactured by Nippon Denshoku Industries Co., Ltd., product name "NDH5000") in accordance with JIS K7361-1:1997. The results are shown in Table 2.

[0148] [Test Example 6] (Measurement of adhesive strength) The light release type release sheet was peeled off from the adhesive sheet produced in the Examples and Comparative Examples, and the exposed light diffusing adhesive layer was attached to an easy adhesion layer of a polyethylene terephthalate (PET) film (manufactured by Toyobo Co., Ltd., product name "PET A4300", thickness: 100 μm) having an easy adhesion layer to obtain a heavy release type release sheet / composite adhesive layer / PET film laminate. The obtained laminate was cut into a width of 25 mm and a length of 100 mm.

[0149] In an environment of 23°C and 50% RH, the heavy release type release sheet was peeled off from the laminate, and the exposed transparent adhesive layer was attached to soda lime glass (manufactured by Nippon Sheet Glass Co., Ltd.), and then pressurized at 0.5 MPa and 50°C for 20 minutes in an autoclave manufactured by Kurihara Seisakusho Co., Ltd. Then, the sample was left for 24 hours under conditions of 23°C and 50% RH, and this was used as a sample. Then, using a tensile tester (manufactured by Orientec Co., Ltd., product name "Tensilon"), the adhesive strength (transparent adhesive layer; N / 25 mm) was measured under conditions of a peel speed of 300 mm / min and a peel angle of 180 degrees (except for Comparative Example 3). The measurement was performed under conditions other than those described here in accordance with JIS Z0237:2009.

[0150] For the adhesive sheet of Comparative Example 3, the above sample was irradiated with active energy rays (ultraviolet rays; UV) through the PET film under the same conditions as in Test Example 1 to cure the composite adhesive layer to form a cured composite adhesive layer. The adhesive strength (N / 25 mm; after UV) of the cured composite adhesive layer was measured in the same manner as above. The results are shown in Table 2.

[0151] Further, for all the pressure-sensitive adhesive sheets, the adhesive strength (N / 25 mm) on the light-diffusing adhesive layer side was measured in the same manner as above (Comparative Example 3 is the adhesive strength after UV curing). The results are shown in Table 2.

[0152] [Test Example 7] (Evaluation of Moire Suppression) The light release type release sheet in the adhesive sheet produced in the Examples and Comparative Examples was peeled off, and the exposed light diffusing adhesive layer was attached to the surface of the display screen of a tablet terminal (Apple Inc., product name "iPad (registered trademark), resolution: 264 ppi). Next, the heavy release type release sheet in the adhesive sheet was peeled off, and a liquid crystal mask having a lattice of 20 ppi to 180 ppi (in 20 ppi increments) was attached to the exposed transparent adhesive layer, to obtain a liquid crystal display.

[0153] The tablet device's screen was set to full green (RGB values ​​(R,G,B) = 0,255,0), and the LCD display was evaluated for moire suppression based on the degree of moire when viewed visually from a direction 60 degrees from the normal to the screen on the LCD mask side, according to the following criteria. The results are shown in Table 2. .circle.: No moire occurred in the liquid crystal displays for all the liquid crystal masks. ◯: No moire occurred in the liquid crystal displays related to most of the liquid crystal masks. ×: Moire occurred in the liquid crystal displays for all the liquid crystal masks.

[0154] [Test Example 8] (Evaluation of image display unevenness prevention) The first and second liquid crystal cells were prepared, and the first liquid crystal cell was adsorbed by an adsorption device. Next, the light release type release sheet in the adhesive sheet produced in the examples and comparative examples was peeled off, and the exposed light-diffusing adhesive layer was attached to one side of the first liquid crystal cell. Next, the heavy release type release sheet in the adhesive sheet was peeled off, and the second liquid crystal cell was attached to the exposed transparent adhesive layer at an attachment speed of 30 mm / sec and a roller pressure of 0.3 MPa using an atmospheric pressure laminator (manufactured by Suntec Co., Ltd., product name "TMS-SA"). Specifically, while one end of the second liquid crystal cell was supported by a glass press, the second liquid crystal cell was pressed against the transparent adhesive layer from the other end side of the second liquid crystal cell by a roller, the roller was rotated and moved to one end of the second liquid crystal cell, and finally the glass press was removed.

[0155] Thereafter, with the first and second liquid crystal cells laminated together, an image was displayed using white light as a backlight, and the displayed image was visually observed from the first liquid crystal cell side, and the prevention of image display unevenness was evaluated according to the following criteria. The results are shown in Table 2. ◎: The image was displayed without any unevenness. ◯: Slight unevenness occurred in the displayed image, but was at a level that caused no practical problems. ×: Unevenness occurred in the displayed image.

[0156] [Test Example 9] (Evaluation of durability) The composite adhesive layer of the adhesive sheet produced in the Examples and Comparative Examples was sandwiched between two soda lime glass plates (manufactured by Nippon Sheet Glass Co., Ltd., thickness: 0.7 mm), autoclaved for 30 minutes under conditions of 50°C and 0.5 MPa, and left at normal pressure, 23°C, and 50% RH for 24 hours.

[0157] The obtained laminates (except for Comparative Example 3) were stored for 1000 hours under high temperature and high humidity conditions of 60°C and 95% RH. The condition of the interface between the composite pressure-sensitive adhesive layer and the adherend (soda-lime glass plate) was then visually inspected, and durability was evaluated according to the following criteria. The results are shown in Table 2. . . . No air bubbles were generated. ◯: A small amount of air bubbles were generated, but the level was not problematic for practical use. ×: Many bubbles were generated.

[0158] For the pressure-sensitive adhesive sheet of Comparative Example 3, the laminate was irradiated with active energy rays through one of the soda lime glass plates under the same conditions as in Test Example 1 to harden the composite pressure-sensitive adhesive layer. Thereafter, the laminate was stored under high temperature and high humidity conditions in the same manner as above, and durability was evaluated. The results are shown in Table 2.

[0159] [Table 1]

[0160] [Table 2]

[0161] As can be seen from Table 2, the pressure-sensitive adhesive sheets produced in the examples were less susceptible to moire and image display unevenness, and also exhibited excellent durability. [Industrial Applicability]

[0162] The pressure-sensitive adhesive sheet according to the present invention can be suitably used in a stereoscopic image display device. [Explanation of symbols]

[0163] 1...Adhesive sheet 2...Composite adhesive layer 21...Light diffusing adhesive layer 22…Transparent adhesive layer 3a, 3b...Release sheet 4. Liquid crystal display components 5a...First liquid crystal cell 5b…Second liquid crystal cell

Claims

1. A pressure-sensitive adhesive sheet having a composite pressure-sensitive adhesive layer including a light-diffusing pressure-sensitive adhesive layer containing light-diffusing fine particles and a transparent pressure-sensitive adhesive layer not containing light-diffusing fine particles, The dynamic hardness (DHT115-1) measured on the surface of the transparent pressure-sensitive adhesive layer side is 0.007 or more, The haze value of the composite pressure-sensitive adhesive layer is 70% or more and 99% or less, the pressure-sensitive adhesive constituting the transparent pressure-sensitive adhesive layer is obtained by crosslinking a pressure-sensitive adhesive composition containing a (meth)acrylic acid ester polymer (A) and a crosslinking agent (B); The (meth)acrylic acid ester polymer (A) contains, as a monomer unit constituting the polymer, a monomer having an alicyclic structure in the molecule. A pressure-sensitive adhesive sheet characterized by:

2. 2. The pressure-sensitive adhesive sheet according to claim 1, wherein the dynamic hardness (DHT115-1) measured on the surface on the side of the light-diffusing pressure-sensitive adhesive layer is 0.007 or more.

3. 3. The pressure-sensitive adhesive sheet according to claim 1, wherein the adhesive strength of the surface on the transparent pressure-sensitive adhesive layer side to soda-lime glass is 1 N / 25 mm or more and 80 N / 25 mm or less.

4. 4. The pressure-sensitive adhesive sheet according to claim 1, wherein the adhesive strength of the surface on the light-diffusing pressure-sensitive adhesive layer side to soda-lime glass is 1 N / 25 mm or more and 80 N / 25 mm or less.

5. 5. The pressure-sensitive adhesive sheet according to claim 1, wherein the composite pressure-sensitive adhesive layer has a thickness of 70 μm or more and 3000 μm or less.

6. It has two release sheets, The composite pressure-sensitive adhesive layer is sandwiched between the two release sheets so as to be in contact with the release surfaces of the release sheets. The pressure-sensitive adhesive sheet according to any one of claims 1 to 5.

7. 7. The pressure-sensitive adhesive sheet according to claim 1, which is used to bond two hard plates together.

Citation Information

Patent Citations

  • Scattering superposed adhesive layer, optical member and liquid crystal display device

    JP2000221308A

  • Elliptically polarized plate and image display

    JP2004177781A

  • Liquid crystal display device

    JP2015114371A

  • Adhesive layer for optical member, optical member with adhesive layer, and image display device

    JP2017043678A

  • Adhesive sheet and liquid crystal display member

    JP2018104602A